Waste disposable methods and challenges among households in selected communities within the Kumasi metropolis - Appiah, Gilbert Debrah (2021)
A thesis submitted to the Department of Health Education, Promotion and Disability, School of Public Health, College of Health Sciences, in partial fulfillment of the requirements for the Degree of Master of Public Health in Health Promotion and Education